Aniba inaequabilis (Lauraceae), a new species from Peru - Matta, Alysson Da; Carvalho, Rangel Batista De; Vicentini, Alberto (Phytotaxa, 2016)
A new plant species from the Amazon in Peru, Aniba inaequabilis, is here described. The new species belongs to a group of Aniba species that has papillose leaves, but differs from all the species described in this group by the combination of stamens with few sparse hairs, stamens of whorl I and II with different shapes and the glands at the base of the inner stamens fused. In this paper the new species is described and illustrated and its relationship with other species of Aniba with papillose leaves is discussed.